Analisis Modus Operandi Penyelundupan Narkotika di Perbatasan Indonesia-Malaysia (Studi Kasus Kabupaten Kepulauan Meranti Provinsi Riau Tahun 2017-2022) - Chandyta Silviani, Rendi Prayuda (UIR Press, 2023)
This study discusses the Analysis of the Modus Operandi of drug smuggling at the Indonesia-Malysia border (Case Study: Meranti Island Regency, Riau Province in 2017-2018). The Meranti Island Regency is a regency in Riau Province with waters directly bordering Malaysia, making it a vulnerable area to Transnational Crimes, particularly drug smuggling originating from Malaysia through maritime routes. Therefore, the researcher focused on studying the Modus Operandi as the reaserch object. The aim of this study to understand to Modus Operandi of drug smuggling at the Indonesia-Malaysia border. The reasercher used the concept of Non-Traditional Security and employed qualitative descriptive research methodology. Additionally, the reseacher conducted literature reviews and a field study to collect data. The results of this study show a variety of drug traffickers' strategies, including internet drug smuggling, hiding drugs in cargo ship, leveraging intermediary connections, and using maritime transportation such as small boats. The actors involved in these activities include transnational actors (non-native citizens), organized crime syndicates, and inmates in prisons. They capitalise on the advantages of waterways and unofficial ports, often known as